Recovery capital and collaborative theatre making: how actors in recovery from substance addiction value their participation in addiction prevention plays. Issue 1 (2nd January 2022) - Snyder-Young, Dani; Houston, Ashley; Bell, Ana Bess Moyer; Short, Andy; Lincoln, Alisa
ABSTRACT: Improbable Players (IP) has been creating applied theatre for substance use disorder prevention since 1984, training more than 200 sober actor/teaching artists to perform plays and facilitate workshops addressing addiction, alcoholism, and the opioid crisis. The company operates, for its actors, as a long-term arts- integrated peer recovery support service and mutual support group for recovery from substance addiction, increasing their recovery capital. This essay examines the ways Improbable Player's applied theatre programme operates to build recovery capital and support individual behavioural changes in its artistic staff.